Blaan Oral Narratives and Their Educational Implications - Sumaljag, Maria Vinice O. (JPAIR Multidisciplinary Research, 2009)
This study aimed to collect, record, translate and analyze the oral narratives of the Blaans in Little Baguio, Malita, Davao del Sur and determine their educational implications. Two types of informants were involved in the research: a) those who told the background of the Blaans and the elders of the tribes, and b) those Blaans who narrated the oral narratives in their own language. Thirty folk narratives were collected ranging from myths, legends and folk tales. Translator/guide assisted in the data gathering while trilingual translators transcribed and translated the oral narratives to Blaan and Cebuano languages. The collected Blaan oral narratives were analyzed by identifying the classification of oral tradition according to genre based on Eugenio’s (1993) general category of folk narratives and the classification the way the Blaans themselves classify their stories in terms of truthfulness and sacredness, and identification and classification of values in the oral narratives according to Andres’ (1985) value matrix. Findings reveal that the oral narratives of the Blaans project their culture and mirror the lifeways of ethnic Filipinos; that common values define their identity as a people; and the collected narratives and their values have educational implications. These narratives can be used as teaching materials/tools in the academe and values drawn can serve as tools for Values Education teachers for the value formation of pupils and students.